Uncertainty Analysis to Assess Depth Conversion Accuracy: A Case Study of Subba Oilfield, Southern Iraq - Al-Khazraji , Omar N. A.; Al-Qaraghuli, Shahad A.; Abdulkareem , Lamees; Idan, Rami M. (Iraqi Journal of Science, 2022)
The depth conversion process is a significant task in seismic interpretation to establish the link between the seismic data in the time domain and the drilled wells in the depth domain. To promote the exploration and development of the Subba oilfield, more accurate depth conversion is required. In this paper, three approaches of depth conversions: Models 1, 2, and 3 are applied from the simplest to the most complex on Nahr Umr Reservoir in Suba oilfield. This is to obtain the best approach, giving less mistakes with the actual depth at well locations and good inter/extrapolation between or away from well controls. The results of these approaches, together with the uncertainty analysis provide a reliable velocity model and more accurate predicted depth that reduced the ambiguity of the subsurface. The uncertainty analysis reveals that Model 3 is considered a more practical and most accurate approach because it gives a minimized standard deviation value of 14 with less residual and error values. The uncertainty of the depth conversion and the standard deviation values is raised towards the eastern part of the field due to an increase in the dipping depth in this region that affects the depth conversion results.